Grain boundary deformation phenomena and secondary growth of goss grains in a Fe-3.5%Si steel - Citrawati, F.; Quadir, Md Zakaria; Munroe, P. (Nippon Tekko Kyokai, 2017)
© 2017 ISIJ. In this investigation, a long-standing grain growth question is addressed in a Fe-3.5% Si steel. This material undergoes secondary growth of Goss oriented grains, but the underlying mechanisms of this growth remain unresolved despite extensive investigations for almost a century. In this investigation, a key question concerning this subject is resolved i.e. whether the nature of primary recrystallization grain boundaries solely determines the growth of Goss grains during secondary recrystallization. To address this issue undeformed and lightly deformed samples were subjected to recrystallization annealing under identical conditions. Although the extent of the deformation is light, such that it creates only limited modifications in the grain boundary structures, the recrystallization mechanism changes from abnormal secondary growth to conventional grain growth. In the former case, recrystallization commences at higher temperatures when the MnS inhibiting particles become dissolved, and in the latter mechanism, recrystallization occurs at lower temperatures due to the differences in stored energy between grains sharing a common boundary. This occurs through strain-induced grain boundary migration.